Контроль параметрів вторинної магнітної рідини при реалізації трипараметрового контактного електромагнітного методу - Себко, Вадим Вадимович; Бабенко, Володимир Миколайович; Мананкова, В. Л. (Науково-інформаційний центр "Знання", 2018)
Исследован контактный электромагнитный трёхпараметровый метод совместного измерительного контроля относительной магнитной проницаемости, удельного электрического сопротивления и температуры образца контролируемой магнитной жидкости, использующий поперечное магнитное поле.

The contact electromagnetic three-parameter method of joint measuring control of the relative magnetic permeability, electrical resistivity and temperature of the sample of controlled magnetic fluid using a transverse magnetic field is investigated.
Control of parameters of the secondary magnetic fluid in the implementation of the three-parameter contact electromagnetic method
Keywords: магнитне поле; охолоджуюча рідина; магнітна проникність; питомий електричний опір; двохчастотний струм; тепловий ТКЕП; magnetic permeability; magnetic field; engine oil; content of metal powder particles; sample; wear parts; temperature; universal conversion functions